La crise de Berlin de 1961 - Legault, Albert (Études internationales, 1979)
The Berlin Wall was but an episode in what is referred to as the Berlin Crisis of 1961. The latter's context included two other conflicts : a domestic power struggle within the Soviet Union and a race for strategic superiority between the superpowers. The methodology employed makes it possible to show that the Berlin Crisis constituted a hiatus within the much larger conflict of the Cold War. It also reveals that the frequency with which objectives were formulated constitutes a very important « indicator » « reference point » or « signpost » within the crisis process. These findings would tend to demonstrate that the stimulus-response model, nothwithstanding its importance, should be completed by a much more methodical examination of the evolution of the objectives pursued by a State in the conduct of its foreign relations.